2011
DOI: 10.3109/17453674.2011.618916
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the intramedullary pressure responses by calcium dobesilate in a rabbit knee model of osteoarthritis

Abstract: Background and purposeThe presence of bone marrow edema in patients with osteoarthritis is associated with pain and disease progression. Management of bone edema with the synthetic prostacyclin iloprost may be complicated by side effects. Calcium dobesilate, a treatment for chronic venous disease, shares some pharmacological actions with iloprost but appears to be better tolerated. Anecdotal reports have suggested that calcium dobesilate may be useful for medical management of osteoarthritis, possibly by reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The decision to measure subchondral forces was based on the unique contour of the canine elbow joint and the disturbance that was caused by our sensors when placed intraarticularly. Subchondral bone pressure has been described in many studies of OA in animals and people . However, most often the pressure was measured with a cannula, located in the subchondral space, attached to a manometer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to measure subchondral forces was based on the unique contour of the canine elbow joint and the disturbance that was caused by our sensors when placed intraarticularly. Subchondral bone pressure has been described in many studies of OA in animals and people . However, most often the pressure was measured with a cannula, located in the subchondral space, attached to a manometer.…”
Section: Discussionmentioning
confidence: 99%
“…Subchondral bone pressure has been described in many studies of OA in animals and people. [35][36][37][38] However, most often the pressure was measured with a cannula, located in the subchondral space, attached to a manometer. Data acquired by this method is only valid for a single point and depends on multiple other factors besides axial compression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus. rabbit models, including anterior cruciate ligament transection and partial meniscectomy models [48,49], have been used to assess the anti-osteoarthritic potential of various drugs [50,51]. To successfully examine the potential effects of drugs against OA, selection of an appropriate animal model is important.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesised that impaired venous drainage causes venous hypertension in the bone marrow resulting in intraosseous hypertension and bone oedema (Svalastoga and Smith 1983, Pleasant et al 1993, Hertsch and Maaß 2009. Anecdotal reports have suggested that the accumulation of osmotically active proteins in the subchondral tissue leads to a compartment syndrome within the subchondral bone which is characterised by increased tissue pressure, acidosis, pain and a vicious cycle of progressive pathological changes (Miles et al 2011). Surgical procedures have been explored to decompress the medullary cavity of the NB in sound horses (Jenner 2007, Jenner andKirker-Head 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this model CD had a detectable effect on pressure dynamics in the subchondral bone of osteoarthritic joints (Miles et al 2011). …”
mentioning
confidence: 99%